Isolation, Characterization, And Production Of Recombinant Monoclonal Antibodies Against Rnie For Development Of A Strongyloides Antigen Detection Assay - Balachandra, Dinesh (2022)
Strongyloides stercoralis is a soil-transmitted helminth that causes strongyloidiasis. It is estimated to infect more than 600 million people worldwide. Asymptomatic chronic infections in immunocompromised people can lead to fatal hyperinfection. Serodiagnosis by detecting specific IgG antibodies can be challenging due to potential cross-reactivity with infections by other parasites. An antigen detection assay, a direct detection method, can help the diagnosis and is useful for post-treatment follow-up. This study used phage display technology to produce recombinant monoclonal antibodies (rMAb) against NIE recombinant protein (rNIE) and develop a Strongyloides antigen detection test. rNIE is an established protein for the diagnosis of strongyloidiasis. rNIE was expressed, purified, and then used to select rMAb candidates via biopanning of an immune helminth phage display library. It isolated of 104 ELISA-positive clones and sequence analysis showed that 30 clones had full-length light and heavy chains. Four unique gene families were identified, i.e., IgHV3-LV6 (86.66%), IgHV1-LV3 (3.33%), IgHV5-KV3 (3.33%), and IgHV3-LV3 (6.66%). Randomly, one representative clone from each gene family was selected for further studies, i.e., (a) rMAb5 representing IgHV1-LV3, (b) rMAb6 representing IgHV3-LV6, (c) rMAb14 representing IgHV5-KV3, and (d) rMAb23 representing IgHV3-LV3. The rMAb gene sequences from the phage display vector were subcloned into the pET51b+ expression vector and transformed into Escherichia coli Shuffle T7 Express host cell.